High‐Performing Clean Water Production by Rational Design of Functional Solar Evaporator and Vapor Condensation - Bingxing Wu; Xiangqian Fan; Chaorui Xue; Qing Chang; Jinlong Yang; Shengliang Hu; Haolan Xu (Advanced Science)
Abstract Interfacial solar evaporation is a promising technology to address the global issue of water scarcity with a minimum carbon footprint. Although solar‐to‐vapor conversion efficiency has been significantly improved, it does not actually lead to high clean water production due to low vapor condensation efficiency and water collection rate, which hinders real‐world applications. Herein, an invert‐structured solar evaporation and vapor condensation device coupled with solar evaporators featuring special vertically aligned vapor diffusion channels is designed to target both high evaporation and water collection rates. Graphene oxides, carbon dots, and MXene are used to construct sophisticated nanostructure to effectively confine the thermal energy in the structure for water evaporation. The vertical channels in the evaporators allow downward vapor transportation for condensation. The bottom condenser, made of highly thermal‐conductive materials with hydrophobic coating, is cooled by bulk water underneath, accelerating the dropwise condensation processes. In addition, since vapor is pushed downward, light absorption on the top evaporation surface is not declined. Both top and bottom evaporation surfaces are activated for water evaporation. Therefore, this inverted device achieves a record‐high water‐collection rate of 2.31 kg m−2 h−1 under one sun, superior to conventional single‐stage solar evaporation systems, suggesting great potential in practical seawater desalination.